Facilitators and Barriers to Post-partum Diabetes Screening Among Mothers With a History of Gestational Diabetes Mellitus–A Qualitative Study From Singapore - Sunny, Sharon Hanna; Malhotra, Rahul; Ang, Seng Bin; Lim, C. S. Daniel; Tan, Y. S. Andrew; Soh, Y. M. Benjy; Ho, X. Y. Cassandra; Gostelow, Martyn; Tsang, L. P. Marianne; Lock, S. H. Smily; Kwek, Suat Yee; Lim, Y. T. Jana; et al. (Frontiers in Endocrinology, 2020)
Introduction Gestational Diabetes Mellitus (GDM) affects 1 in 6 births worldwide. Mothers with GDM have an increased risk of developing post-partum Type-2 Diabetes Mellitus (T2DM). However, their uptake of post-partum diabetes screening is suboptimal, including those in Singapore. Literature reports that the patient-doctor relationship, mothers’ concerns about diabetes, and family-related practicalities are key factors influencing the uptake of such screening. However, we postulate additional factors related to local society, healthcare system and policies in influencing post-partum diabetes screening among mothers with GDM. Aim The qualitative research study aimed to explore the facilitators and barriers to post-partum diabetes screening among mothers with GDM in an Asian community. Methods In-depth interviews were carried out on mothers with GDM at a public primary care clinic in Singapore. Mothers were recruited from those who brought their child for vaccination appointments and their informed consent were obtained. Both mothers who completed post-partum diabetes screening within 12 weeks after childbirth and those who did not, were purposively recruited. The social ecological model (SEM) provides the theoretical framework to identify facilitators and barriers at the individual, interpersonal, organizational and policy levels. Results Twenty multi-ethnic Asian mothers with GDM were interviewed. At the individual and interpersonal level, self-perceived risk of developing T2DM, understanding the need for screening and the benefits of early diagnosis, availability of confinement nanny in Chinese family, alternate caregivers, emotional and peer support facilitated post-partum diabetes screening. Barriers included fear of the diagnosis and its consequences, preference for personal attention and care to child, failure to find trusted caregiver, competing priorities, and unpleasant experiences with the oral glucose tolerance test.. At the organizational and public-policy level, bundling of scheduled appointments and standardization of procedure eased screening but uptake was hindered by inconvenient testing locations, variable post-partum care practices and advices in the recommendations of diabetes screening. Conclusion Based on the SEM, facilitators and barriers towards post-partum diabetes screening exist at multiple levels, with some contextualized to local factors. Interventions to improve its uptake should be multi-pronged, targeting not only at personal but also familial, health system and policy factors to ensure higher level of success.